The effect of interventional treatment in acute myocardial infarction on ST resolution: A comparison of coronary angioplasty with excimer laser angioplasty - Ilkay, E; Karaca, I; Yavuzkir, M; Akbulut, M; Pekdemir, M (Sage Publications Inc, 2005)
The treatment methods for acute myocardial infarction (MI) have started to change in the new millennium. Myocardial perfusion (ST-segment resolution) is the target rather than achieving TIMI-III flow in the infarct-related artery, In this study the authors compared the effect of percutaneous transluminal coronary angioplasty (PTCA) and excimer laser angioplasty (ELCA), which was accepted as one of the thrombolysis methods, on ST-segment resolution. A stent was applied after ELCA to 36 patients (4 women, 32 men; mean age 50.44 +/- 9.8 years) in group I and a stent was applied after balloon angioplasty to 44 patients (5 women, 39 men; mean age 50.77 +/- 12.2 years) in group II. Fisher's exact test was used in the analysis of data, and p < 0.05 was accepted as significant. There was no difference between the groups with respect to symptom duration, time to angioplasty, risk factors, infarct localization, stent diameter, and length. TIMI-III flow was achieved in 33 patients (92%) in group I and in 40 patients (91%) in group II. There was no statistical difference in TIMI flow between the groups. In group I, complete ST resolution was observed in 75% (27/36) of the patients, partial resolution in 22% (8/36), and resolution was unsuccessful in 3% (1/36). In group 11, complete, partial, and unsuccessful ST resolution were 41% (18/44), 45% (20/44), and 14% (6/44), respectively. The mean ST resolution was 82.78 +/- 11.8% in group I and 66.36 +/- 10% in group II (p = 0.001). ST segment resolution, which is a good predictor of tissue perfusion, was higher with ELCA than with balloon angioplasty. These findings should be supported by large randomized studies.
Keywords: No-Reflow Phenomenon; Thrombolytic Therapy; Embolization; Reperfusion; Predictor; Perfusion; Impact; Risk